2012
DOI: 10.1038/ejcn.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fasting plasma alkylresorcinol metabolites concentrations measured 4 months apart

Abstract: Alkylresorcinols (AR) have been suggested as specific dietary biomarkers of whole-grain wheat and rye intake. AR are metabolised to 3,5-dihydroxybenzoic acid (DHBA) and 3-(3,5-dihydroxyphenyl)-1-propanoic acid (DHPPA), which have longer apparent half-lives and were recently proposed to better reflect long-term whole-grain consumption than the intact AR. The objective of this study was to analyse the reliability-expressed by the intraclass correlation coefficient (ICC)-of AR metabolite concentrations among 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…The nonsignificant association might result from a lack of the increased benefits of whole-grain intake when increasing intake from intermediate or high levels (5,25). In our population, plasma DHPPA concentration was significantly lower compared with that in European populations (21.9 nmol/L in elderly Swedish men [19] and 50.6 nmol/L in German men and women [29]). This could be attributed to dietary patterns in Asian countries where rice and wheat are the staple foods.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The nonsignificant association might result from a lack of the increased benefits of whole-grain intake when increasing intake from intermediate or high levels (5,25). In our population, plasma DHPPA concentration was significantly lower compared with that in European populations (21.9 nmol/L in elderly Swedish men [19] and 50.6 nmol/L in German men and women [29]). This could be attributed to dietary patterns in Asian countries where rice and wheat are the staple foods.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study has several strengths. Plasma concentration of alkylresorcinol metabolites is a novel and independent biomarker of whole-grain intake with modest long-term reproducibility (29), and it has been used in several studies to estimate the effect of whole-grain wheat and rye on human health (19,36). Moreover, participants in this study were confined to the newly diagnosed to avoid possible changes in diet and lifestyle, which may distort the association between whole-grain intake and T2D risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mean concentrations of the metabolites did not differ significantly over the 4-month period, these results indicate a fairly poor reliability. The results from the study by Montonen and colleagues may however, not be transferable to the current study with a different population and a different methodology for the analyses of metabolite concentrations (36). However, additional studies are needed on the validity of alkylresorcinol metabolites as a biomarker for whole grains.…”
Section: Discussionmentioning
confidence: 54%
“…Studies on AR, its homologs, and metabolites generally showed a moderate short-term reproducibility, but a relatively poor reproducibility in the assessment of the medium-to long-term exposure to WG in the blood and urine [35,55,83,84]. To our knowledge, no study assessed the reproducibility of avenacosides and benzoxazinoid compounds.…”
Section: Discussionmentioning
confidence: 95%